Apifloristic diversity in the eastern Mediterranean region: implications for biodiversity conservation and use - Topal, Ali; Uzun, Alper; Polat, Osman (Archives of Biological Sciences, 2023)
Paper description: Honey plants around the world are well known. However, there is no information about the link between the apifloral diversity and endemism in the Eastern Mediterranean honeybee forests. 78 sample plots assigned to 10 honeybee forests scattered in different elevations and districts of Mersin were studied. A total of 511 plant species were identified, of which 334 were melliferous and 50 were endemic. Honeybee forests in the Eastern Mediterranean differed in terms of apifloral diversity and endemism, especially according to elevation and district criteria. Higher elevations showed a more diverse and more nectar-rich plant distribution. Abstract: The ecological role of honeybees in the world and their value for sustainable agriculture and food industry are more important than ever. For this reason, we study the apiflora in the eastern Mediterranean region of Türkiye in the context of planning bee forests aimed at biodiversity conservation. The results show that honeybee forests are quite rich in both endemism and apifloristic diversity. A total of 511 plant taxa belonging to 264 genera and 59 families were identified, of which 335 (65%) taxa were evaluated as nectar (N) and/or pollen (P) bearing honey plants (45 N, 54 P, and 236 N&P). In terms of apiflora, the richest families are Fabaceae (n=76, 3 N, 73 N&P), Lamiaceae (n=57, 19 N, 38 N&P) and Asteraceae (n=44, 1 N, 10 P, 33 N&P). Nectariferous plants were more common at higher elevations, while polleniferous plants were more common at lower elevations. According to the Shannon-Wiener diversity index, the highest diversity values were found in honeybee forests at higher elevations and the lowest diversity values at lower elevations. Sorensen analysis also showed that floristic similarities among honeybee forests ranged from 1% to 42%. Cluster analysis supported these differences by dividing the forests into two separate groups.